2016
DOI: 10.1007/s00701-016-2871-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for post-operative respiratory failure among 94,621 neurosurgical patients from 2006 to 2013: a NSQIP analysis

Abstract: Based on the NSQIP database, risk factors for respiratory failure after neurosurgery include pre-operative ventilator dependence, alcohol use, functional dependence prior to surgery, stroke, and recent operation. The overall rate of respiratory failure decreased from 4.1 % in 2006 to 2.1 % in 2013 according to these data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Impact of alcohol use on 30-day complication and readmission rates after elective spinal fusion (≥2 levels) for adult spine deformity: a single institutional study of 1,010 patients (7)(8)(9), colorectal surgery (4,10,11), obstetric surgery (12), transplant surgery (13), head and neck surgery (14)(15)(16), orthopedic surgery (17)(18)(19) and neurological surgery (20). A few studies even suggest a dose-dependent effect of alcohol use on postoperative complication rates (11).…”
Section: Original Studymentioning
confidence: 99%
“…Impact of alcohol use on 30-day complication and readmission rates after elective spinal fusion (≥2 levels) for adult spine deformity: a single institutional study of 1,010 patients (7)(8)(9), colorectal surgery (4,10,11), obstetric surgery (12), transplant surgery (13), head and neck surgery (14)(15)(16), orthopedic surgery (17)(18)(19) and neurological surgery (20). A few studies even suggest a dose-dependent effect of alcohol use on postoperative complication rates (11).…”
Section: Original Studymentioning
confidence: 99%
“…Among SRS patients, vertebral compression fracture is a well-known postoperative complication that has been associated with age greater than 55 years [18]. In another NSQIP study, Cote et al [19] found that among 98,000 neurosurgical patients, older age and dependent functional status predicted postoperative respiratory failure. In the present analysis, we found that functional dependence prior to SRS was predictive of readmission within 30 days (42% greater odds) and of prolonged LOS (40% greater odds).…”
Section: Discussionmentioning
confidence: 99%
“…17 Furthermore, functional status has been demonstrated to be associated with unplanned postoperative intubations and respiratory failure in various NSQIP studies looking at all major noncardiac surgeries, neurosurgery, and complex general and vascular surgery. 13,[18][19][20] Thyroid-and parathyroidectomies are not high-risk surgical procedures; 21 however, there are complications unique to this patient population, since airway compromise due to respiratory failure related to surgical hematoma, 22,23 recurrent laryngeal nerve injury, and hypocalcemia-induced laryngospasm are possible. 24 Usually, these specific surgical complications occur within the first 48 h. Our data show that there was no difference in unplanned intubation rates between matched cohorts during the first 2 hospital days.…”
Section: Discussionmentioning
confidence: 99%